The Good and the Bad: Environmental Efficiency in Northeastern U.S. Dairy Farming. (29th April 2016) - Njuki, Eric; Bravo-Ureta, Boris E.; Mukherjee, Deep
Abstract : This study evaluates the environmental performance of northeastern U.S. dairy operations that differ in size using a directional output-distance function that measures the joint production of milk and emissions while incorporating a four-way error approach that captures farm-size heterogeneity, transient and persistent technical efficiency, and random errors. For the emission component, a comprehensive pollution index is generated that incorporates three major sources of pollution in dairy farming: fuel, fertilizer, and livestock. Computed shadow prices and Morishima elasticities of substitution reveal that large dairy operations are environmentally inefficient compared to their smaller counterparts.